AB1364 Death analysis of 144 rheumatoid arthritis patients over the last 24 years. (23rd January 2014) - Hayashi, M.; Kojima, T.; Ishiguro, N.; Hirano, Y.; Kobayakawa, T.; Kanamono, T.
Abstract : Background: Life expectancy for rheumatoid arthritis (RA) patients is 10 years less than that for other adults. However, there have been major pharmacotherapeutic and surgical advances in the treatment of RA patients. In this study, we investigated life expectancy and death trends in RA patients at a single Japanese institute. Objectives: To investigate trends associated with life expectancy in RA patients by reviewing the records of 144 patients who died over the past 24 years at Nagano Red Cross Hospital. Methods: Of all 899 RA patients at our institute, the records of 144 patients who died over the past 24 years were reviewed in this study. The records of these patients were divided into two groups: 73 patients who died before the end of 2002 and 71 patients who died after the beginning of 2003. We estimated the gender, age, RA duration, and cause of death by confirming with their relatives via the telephone and not based on the death certificate. Results: The average ± SD of the 73 patients who died before the end of 2002 and the 71 patients who died after the beginning of 2003 were as follows: male ratio 23.6% vs. 36.6% for those in the former versus latter group; age at death 72.0±10.5 years vs. 77.0±9.01 years; RA duration (from RA onset to death) 15.7±10.9 years vs. 20.7±12.7 years; and death from infection 24.7% vs. 39.4%. The latter group was significantly higher than the former group in these aspects, but no significant difference in the cancer death rate was noted (16.4% vs. 15.5%). The latter included three cases patients with a history of treatment with biological agents, all of whom had been treated with etanercept (ETN) alone. Two of these patients died from pneumonia and one from sepsis. Conclusions: In July 2003, infliximab, which is now one of 6 biological agents approved for RA treatment in Japan, was approved first for use. Because RA duration and age at death among RA patients were equally prolonged by five years after 2003 than before 2003, life expectancy of RA patients from the onset of RA may have been improved through developments in RA treatment, such as the use of biological agents. However, the first cause of death was infection in both groups and was also the cause of death of the three patients treated with ETN alone. Death caused by cardiovascular events was low throughout both periods, unlike in Europe. Disclosure of Interest: None Declared